Barley powdery mildew control in Western Australia and beyond - Ellwood, Simon; Lopez-Ruiz, Francisco; Tan, Kar-Chun (2024)
Australia is one of the largest barley exporters in the world, with Western Australia accounting for some 40% of national production. The crop is predominantly grown in the south and south-west of the state in winter and spring, where temperate conditions and higher rainfall levels are more suited to barley than northern and eastern regions. Between 2007 and 2013, prolonged outbreaks of barley powdery mildew (BPM) occurred. This was brought about by a combination of the extensive use of susceptible cultivars and an over-reliance on a small number of single mode-of-action demethylation inhibitor fungicides, which select for mutations in the C14α-demethylase (Cyp51A) gene. This review highlights the steps taken to reduce losses to BPM, breeding efforts to introduce resistance into cultivars and the success of pre-breeding research to find new and durable resistance genes. We also draw comparisons with powdery mildew in Australian wheat, where similar factors are leading to substantial outbreaks.